ANALISIS NORMATIF TERHADAP PERCERAIAN KARENA PENGUNAAN MEDIA SOSIAL - Siti Anisa; Musyfikah Ilyas; Nurfaika Ishak (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2022)
Building a happy and harmonious household is everyone's dream. However, in the course of domestic life, it does not always run smoothly, there are problems that adorn every journey, even to the decision to divorce. The problem studied in this study is to analyze divorce due to the normative use of social media and how judges consider in deciding divorce cases due to social media in the decision of the Sidenreng Rappang Religious Court. This research is a type of normative-empirical legal research with qualitative research methods. The results of this study explain that there are several divorce decisions that were triggered by the use of social media at the Sidenreng Rappang Religious Court. Social media here is not the main factor of a divorce but as a factor causing the divorce. The panel of judges in resolving divorce cases triggered by the use of social media is based on the facts in the trial that became the reason for the divorce. In divorce cases due to domestic disputes, the judge will refer to Article 19 letter (f) of Government Regulation Number 9 of 1975 concerning the Implementation of Law Number 1 of 1991 concerning the Compilation of Islamic Law. In Islamic law, the use of social media depends on the user's intentions. There needs to be awareness in the community in using social media, especially for married couples. Sometimes using social media is out of bounds and the obligations of husband and wife are neglected.